Isolation and investigation of external reproduction tract mycoflora in healthy male cats - Massoud Talebkhan Garoussi; Aghil Sharifzadeh; Mahssa Khodabakhsh; Abdol Ali Malmasi (Veterinary Medicine and Science, 2024)
Abstract Background Various infectious agents can infect the male reproductive system. Objectives The aims of this study were to provide current data on fungal and yeast flora of the external organs of reproductive system of male short hair cats including penis and prepuce. Methods In total 28 samples were taken from external genital system of male stray cats using sterilised cotton swabs. Samples were taken based on the absence of any reproductive complications using physical examinations. The samples were transferred to sterilised Stuart transport media and were then incubated in the Sabouraud dextrose agar with chloramphenicol at 32°C for 48 h. The identification of fungi and yeasts was confirmed by germ tube formation test, CHROM agar, urease testing and Corn meal agar medium with Tween 80. Results Fungal agents were isolated from 7 (25%) out of 28 male stray cats. Fungal isolates were obtained from the penis and prepuce of 4 (36%) and 7 (100%) male cats, respectively. The most commonly recovered species samples were Candida krusei (3.75%) and Penicillum spp. (6.86%) from the penis and prepuce of the cats, respectively. The external organs of male reproduction of cats were infected with 2–4 different fungal agents. Only 5 (45%) cats were infected with one fungus; however, in 6 (55%) cats, mixed fungal infections were isolated. Cats 3–4 years old had the highest fungal contamination in the prepuce region (4/7), while the penis at this age had the least contamination (1/4). Conclusions It is concluded that the external reproduction organs of male cats could be infected by different fungal agents.